2005
DOI: 10.1016/j.cell.2005.09.023
|View full text |Cite
|
Sign up to set email alerts
|

A Minicircuitry Comprised of MicroRNA-223 and Transcription Factors NFI-A and C/EBPα Regulates Human Granulopoiesis

Abstract: MicroRNAs play important roles in cell differentiation by acting as translational inhibitors of specific target genes. Here we show that human granulocytic differentiation is controlled by a regulatory circuitry involving miR-223 and two transcriptional factors, NFI-A and C/EBPalpha. The two factors compete for binding to the miR-223 promoter: NFI-A maintains miR-223 at low levels, whereas its replacement by C/EBPalpha, following retinoic acid (RA)-induced differentiation, upregulates miR-223 expression. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
952
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 935 publications
(1,000 citation statements)
references
References 42 publications
41
952
2
5
Order By: Relevance
“…Although NFI-A maintains miR-223 at low levels, its replacement by C/EBPa following RA differentiation, upregulates miR-223 (Fazi et al, 2005). Consistent with these data, we confirmed that miR-223 is induced significantly upon treatment with ATRA.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Although NFI-A maintains miR-223 at low levels, its replacement by C/EBPa following RA differentiation, upregulates miR-223 (Fazi et al, 2005). Consistent with these data, we confirmed that miR-223 is induced significantly upon treatment with ATRA.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, the ectopic expression of miR-181a in murine hematopoietic progenitor cells led to a proliferation in the B-cell compartment (Chen et al, 2004). More recently, it has been reported that miR-223 is a key member of a regulatory circuit involving C/EBPa and NFI-A that controls granulocytic differentiation in ATRA-treated APL cell lines (Fazi et al, 2005). Little is known, however, about other miRNAs expression in ATRAtreated APL cells.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors that regulate the activity of miRNA promoters have recently been described (47,48). Moreover, several miRNA have been shown to regulate the 3Ј-UTR of mRNA that encode transcription factors (49), and a circuit that sequentially involves miRNA and transcription factors in a mutual negative feedback loop has been described (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several miRNA have been shown to regulate the 3Ј-UTR of mRNA that encode transcription factors (49), and a circuit that sequentially involves miRNA and transcription factors in a mutual negative feedback loop has been described (48,49). As for the transcription factors, it has been reported that REST inhibits miR124a expression in non-neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , reciprocal negative feedback between mir-7 and its target Yan reinforces the photoreceptor differentiation induced by the EGF signal in developing eyes [73]. A similar negative feedback regulatory circuitry involving miR-223 and two transcriptional factors, NFI-A and C/EBPα, is important in human granulocytic differentiation [74]. In C. elegans , a positive feedback loop between lin-12, mir-61 , and vav-1 was reported to maximize LIN12 activity and specify the secondary vulva cell fate [75].…”
Section: Discussionmentioning
confidence: 99%